2003
DOI: 10.1034/j.1600-0420.2003.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

The mystery of myopia

Abstract: ABSTRACT.Published data from all parts of the world show that myopia is rare before school age, gradually increases during school life and reaches its highest level of prevalence during the years of most intense study at university. It is widely held that continuous reading harms the eyes, but none of the attempts made so far to reduce accommodative fatigue by introducing pauses during reading and teaching, eye exercises, etc. have been successful in reducing the number of children who develop myopia. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 16 publications
2
34
0
1
Order By: Relevance
“…from the reported records. In summary, 2 of 3 of our high myopes (|SER| > 6 D.) develop serious vision problems, as is often reported (Holden et al, 2014; Wong et al, 2014; Goldschmidt, 2003), 4 of 5 employ (+) Add lenses for 10 to 30 years, with refraction remaining stable. This post-graduate age bracket corresponds to that of pilots, so ordinary reading glasses may be a simple, practical solution to stabilize pilot myopia.…”
Section: Resultssupporting
confidence: 58%
“…from the reported records. In summary, 2 of 3 of our high myopes (|SER| > 6 D.) develop serious vision problems, as is often reported (Holden et al, 2014; Wong et al, 2014; Goldschmidt, 2003), 4 of 5 employ (+) Add lenses for 10 to 30 years, with refraction remaining stable. This post-graduate age bracket corresponds to that of pilots, so ordinary reading glasses may be a simple, practical solution to stabilize pilot myopia.…”
Section: Resultssupporting
confidence: 58%
“…Especially myopia has become a very common problem. Several studies describe an increasing prevalence of myopia in the last two decades (Sveinsson 1982; Hosaka 1988; Fledelius 1983; Morgan and Munro 1973; Johnson et al 1984; van Rens 1991; Lin et al 2004; Rose et al 2001; Saw et al 2005) whereas other studies concluded that the frequency of myopia had been nearly static for a century (Midelfart et al 1992; Goldschmidt 2003; Fledelius 2000). Furthermore, racial differences in myopia rates are well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Although the true aetiology of myopia is still unknown (Goldschmidt 2003), the cornea is responsible for approximately two-thirds of optical refraction and its role in myopia has consequently been studied intensely over the years. Known possible changes in the highly myopic eye are all located in the posterior segment: staphyloma, myopic conus, choroidal atrophy, thinning of the retina and sclera.…”
Section: Introductionmentioning
confidence: 99%